Praktik MSDM Berorientasi Keluarga dan Implikasinya pada Work-life balance dan Keterikatan Kerja - Ila Sri Apriani; Susanti Saragih (Yayasan Literasi Sains Indonesia, 2026)
This study aims to analyze the influence of family-oriented Human Resource Management (HRM) practices on employee work engagement and work-life balance, as well as to examine the role of gender as a moderating variable. Data were collected from 85 employees working across various organizations in Bandung City and analyzed using SmartPLS 4 software, encompassing a series of tests including validity, reliability, and hypothesis testing. The findings indicate that family-oriented HRM practices do not have a significant direct effect on either work engagement or work-life balance. Nevertheless, gender was found to moderate the relationship between family-oriented HRM practices and work engagement, although this moderating effect was not observed for work-life balance. These findings affirm that generic and uniform policy approaches tend to be less effective in optimally supporting employees' professional and personal lives, given that the needs of male and female employees are fundamentally different from one another. Therefore, this study provides strategic insights for managers and policymakers to design and promote more inclusive and gender-responsive HRM practices in order to create a conducive work environment that supports the well-being of all employees.